POSSIBILITIES OF SOCIAL INCLUSION THROUGH A PROGRAM SPORTS EDUCATION: PERCEPTIONS OF EDUCATORS. (Fiep Bulletin - online, 2015)
The present study aimed to examine the perceptions of teachers of an educational sporty design of the possibilities of inclusion and the benefits that sports can give participants the same. 24 professional physical education were investigated with a mean age of 22 years, which was observed is that the former professional positive sports experiences makes them see the project as a positive way the lives of the students involved understand the sports as a means to strengthen the feelings of respect and responsibility 25%, 22.5% integration and inclusion and contribute to social change 15%. Were still the benefits of sports best suited discipline / respect / responsibility 23,28% indicated in the vision of being teachers and students in the permanence of these projects are related to the processes of social integration / friendship 25.35%, being quoted still learning the factor 16.90% and the quality of teachers / work on the project with 14.08%. The teachers were unanimous in affirming the perceived these students during the course of project development, motivation presented by sports practice, the organization of the proposed activities and future possibilities of learning to be applied in your daily life, makes clear the importance of holding projects aimed at the integral development of the student, ie beyond sports practice that respects social, emotional, moral, are widely exploited for them to be really worked like whole subject.
Keywords: social projects; social inclusion; full training